Truth and Reconciliation Commission, 2015 [Canada] - Angus Reid Institute (Borealis, 2016)
Canadians believe the recently concluded Truth and Reconciliation Commission was a worthwhile process for their country, and most support its key recommendations, but that doesn’t mean they anticipate the federal government taking action. This poll looks at Canadian’s attitudes towards the Truth and Reconciliation Commission, its process and recommendations, and Aboriginal people in Canada.